IMPROVING STUDENTS READING COMPREHENSION ON REPORT TEXT THROUGH KWL READING STRATEGY - Indriyati, Fitri; Bunau, Eusabinus Bunau; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Abstract: The purpose of this research is to help students to cope with their problem in reading comprehension through KWL reading strategy. This research was a classroom action research which was conducted on the purpose to solve the problems that happened in the classroom and to improve the teaching-learning process. The data were collected through achievement test, field notes, and observation checklist. The use of KWL reading strategy in improving students reading comprehension can be seen in every meeting that was observed. Based on the research findings, the KWL reading strategy which was applied to the subject of research showed the improvement the students reading comprehension of report text. The data mean score showed at the students test of first cycle was 54.28 and get improved at second cycle test that was 78.9 and third cycle students mean score was 80.7. Meanwhile, the standard score given was 75. It means that by using KWL reading strategy in teaching reading comprehension in report text the students get improved from time to time. Key words: Reading comprehension, report text, KWL. Abstrak: Penelitian ini bertujuan untuk membantu siswa mengatasi masalah mereka di dalam pemahaman membaca melalui strategi membaca KWL. Penelitian ini merupakan penelitian tindakan kelas di mana diselenggarakan dengan tujuan untuk mengatasi masalah yang terjadi di kelas dan meningkatkan proses pengajaran-pembelajaran. Data dari penelitian tindakan kelas di kumpulkan dengan tehnik observasi langsung di dalam kelas melalui tes prestasi, catatan lapangan, dan observasi. Kegunaan dari strategi membaca KWL di dalam meningkatkan pemahaman membaca siswa dapat dilihat di tiap pertemuan yang telah di observasi. Bedasarkan temuan penelitian, strategi membaca KWL di mana telah dipergunakan pada subjek penelitian menunjukan peningkatan pemahaman membaca report teks. Data skor rata-rata menunjukan pada tes pertama siswa yaitu 54,28 dan mendapat peningkatan pada tes putaran kedua yaitu 78,9 dan tes putaran ketiga rata-rata skor yaitu 80,7. Sementara itu, standar skor yang diberikan adalah 75. Ini berarti dengan menggunakan strategi membaca KWL dalam mengajar pemahaman membaca siswa di dalam teks report dapat meningkat dari waktu ke waktu. Kata kunci: Pemahaman membaca, teks report, KWL.